Negative Immune Checkpoint Protein, VISTA, Regulates the CD4+ Treg Population During Sepsis Progression to Promote Acute Sepsis Recovery and Survival - Gray, Chyna C.; Biron-Girard, Bethany; Wakeley, Michelle E.; Chung, Chun-Shiang; Chen, Yaping; Quiles-Ramirez, Yael; Tolbert, Jessica D.; Ayala, Alfred (Frontiers in Immunology, 2022)
Sepsis is a systemic immune response to infection that is responsible for ~35% of in-hospital deaths and over 24 billion dollars in annual treatment costs. Strategic targeting of nonredundant negative immune checkpoint protein pathways can cater therapeutics to the individual septic patient and improve prognosis. B7-CD28 superfamily member, V-domain Immunoglobulin Suppressor of T cell Activation (VISTA), is an ideal candidate for strategic targeting in sepsis. We hypothesized that immune checkpoint regulator, VISTA, controls T-regulatory cells (Treg), in response to septic challenge; thus, playing a protective role/reducing septic morbidity/mortality. Further, we investigated if changes in morbidity/mortality are due to a Treg-mediated effect during the acute response to septic challenge. To test this, we used the cecal ligation and puncture model as a proxy for polymicrobial sepsis and assessed the phenotype of CD4+ Tregs in VISTA-gene deficient (VISTA-/-) and wildtype mice. We also measured changes in survival, soluble indices of tissue injury, and circulating cytokines in the VISTA-/- and wildtype mice. We found that in wildtype mice, CD4+ Tregs exhibit a significant upregulation of VISTA which correlates with higher Treg abundance in the spleen and small intestine following septic insult. However, VISTA-/- mice have reduced Treg abundance in these compartments met with higher expression of Foxp3, CTLA4, and CD25 compared to wildtype mice. VISTA-/- mice also have a significant survival deficit, higher levels of soluble indicators of liver injury (i.e., ALT, AST, Bilirubin), and increased circulating proinflammatory cytokines (i.e., IL-6, IL-10, TNFα, IL-17F, IL-23, and MCP-1) following septic challenge. To elucidate the role of Tregs in VISTA-/- sepsis mortality we adoptively transferred VISTA-expressing Tregs into VISTA-/- mice. This adoptive transfer rescued VISTA-/- survival to wildtype levels. Taken together, we propose a protective Treg-mediated role for VISTA by which inflammation induced tissue injury is suppressed and improves survival in early-stage murine sepsis. Thus, enhancing VISTA expression or adoptively transferring VISTA+ Tregs in early-stage sepsis may provide a novel therapeutic approach to ameliorate inflammation-induced death.